Vegetius and the Anonymus De Rebus Bellicis - Milner, N (1991)
The name, title, literary persona and office of Vegetius are discussed in ch. 1, and although a firm decision is unjustified, comes stabuli seems bettter-attested than praefectus praetorio, come sacrarum largitionum or comes rei privatae. It is suggested that 'Vegetius' is only a cognomen to a true gentilicium 'Flavius'. The author's self-presentation as the Emperor's director of studies-cum-secretary is noticed. Ch. 2 provisionally locates Vegetius in Spanish horse-breeding senatorial circles, and treats his conventional Latin education with little or no Greek, his Vergil-reverence and orthodox Christianity. The date of Vegetius' Epitoma Rei Militaris is analysed in ch. 3 as being before the sack of Rome but in the aftermath of the battle of Adrianople. The Emperor-dedicatee is provisionally identified as Theodosius I. Scholarly debate on the question is thoroughly aired. The genre, literary persona and date of the Anonymus De Rebus Bellicis are argued in ch. 4 against the comparison of Vegetius. The Anonymus is characterized as a thaumaturgical sophist who complied his 'inventions' from older mechanical sources. A late-4th. or early 5th. century date is supported in opposition to the A.D. 360's. Ch. 5 argues that Vegetius' Epitome was intended to describe a Republican legionary organization adapted to late-antique Field armies with the unstated aim of reversing in detail and with specific advantages in mind the rapidly increasing barbarization of the army. Ch. 6 addresses the extent to which tactics and strategic constraints, arms and equipment and siegecraft were understood by Vegetius in contemporary terms, particularly as shown by Ammianus Marcellinus. It is argued in ch. 7 that the sources Vegetius used were late epitomes of the named sources, Cato, Celsus, Frontinus and Paternus, apart from Varro whom he used directly. Massive authorial intervention by Vegetius in the organization and content of the text is analysed.